Criminalité et police à Londres au XIXe siècle - Philippe Chassaigne (Revue Française de Civilisation Britannique)
The British people were extremely reluctant to accept the very idea of a professional police force, smacking as it did of authoritarianism à la française. London, where law and order was felt to be most at risk, was used as a testing ground for such a reform by the Home Secretary, Robert Peel, in 1829. The experience was successful, so that the numbers and the powers of the Metropolitan Force were gradually extended, while the London police was taken as a model, albeit rather slowly, by other local authorities in England (Scotland and Ireland retaining their own system of police organisation). At the end of the 19th century, the decline in theft and violence displayed in the Criminal Statistics resulted in something akin to a ‘love story’ between the English and their police, which was to last until the more troubled 1960s.